2020
DOI: 10.20944/preprints202004.0257.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictive Analytics of COVID-19 Using Information, Communication and Technologies

Abstract: Globally, there is massive uptake and explosion of data and challenge is to address issues like scale, pace, velocity, variety, volume and complexity of the data. Considering the recent epidemic in China, modeling of COVID-19 epidemic for cumulative number of infected cases using data available in early phase was big challenge. Being COVID-19 pandemic during very short time span, it is very important to analyze the trend of these spread and infected cases. This predictive analytics can be empowered using Infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Tremendous work has been going on the COVID-19 apart from the above discussed work [77][78][79][80][81][82]. Researchers are working to investigate efficient and accurate models in order to predict the death count.…”
Section: Data Science/machine Learning Techniquesmentioning
confidence: 99%
“…Tremendous work has been going on the COVID-19 apart from the above discussed work [77][78][79][80][81][82]. Researchers are working to investigate efficient and accurate models in order to predict the death count.…”
Section: Data Science/machine Learning Techniquesmentioning
confidence: 99%
“…M. P.N. et al, 2020 [14] To present different predictive analytics techniques available for trend analysis, different models and algorithms and their comparison.…”
Section: A-sir Modelmentioning
confidence: 99%
“…In this study, they shown that if fever is yes, cough is yes then the probability of coronavirus infection seems to be positive, similarly, if fever is greater than 38 and cough is dry which comes in the category of yes and patient is facing difficulty in breathing and he has also a travel history to some infected countries than the result shows the positive probability of coronavirus infection. Mahalle P. N. et al [79] proposed a model on April 16. They proposed different predictive analytics techniques available for trend analysis, different models and algorithms, and their comparison.…”
Section: Machine Learning Based Modelsmentioning
confidence: 99%
“…Al. [79]. They have used the model to study the data related to Madhya Pradesh, India, and tried to estimate the number of days in which the cases will be removed based on different recovery rates.…”
Section: Other Modelsmentioning
confidence: 99%